Carbon emission management of coal power plant from the perspective of production planning in China. (2nd January 2023) - Zhang, Xiaolong; Dou, Yadong; Zhang, Chuchen; Ding, Liwei; Lv, Hongkun
ABSTRACT: The operation of the national carbon emission trading market has brought new pressure to coal power plants in China. How to control the carbon emissions of the plants and ensure their power generation has become an important issue. This paper proposed a new production profit model based on risk constraint to explore a decision-making method for the plant's carbon emission and production. A branch-and-cut algorithm is applied in the optimization solver to achieve a large-scale constraint linear programming, where the conditional value-at-risk is evaluated by Monte Carlo simulation. Results from the numerical analyses of the coal plant of 4520 MW capacity show that, the carbon emission according to our method is reduced by 3.94%, while the annual profit is increased by 1.25% and the overall cost is decreased by 1.06%. The proposed approach is helpful for the coal plants to manage their carbon emissions and optimize their power production. Abstract : uf0001